(untitled) (Journal of Science and Technology Research, 2024)
The study was conducted to provide a histomorphmetric comparison between the mucosa of the gastrointestinal tract (GUT) and the distribution pattern of gutassociated lymphoid tissue (GALT) in two types of chickens in Bangladesh: Sonali and Indigenous chickens. The study included 20 male Sonali and indigenous chickens aged 10 to 11 weeks, divided evenly into two groups of 10 chickens each. Following humane slaughter, various segments of the GUT were collected for histomorphometric analysis with hematoxylin and eosin staining. The histological investigation revealed that the epithelial lining and mucosal layer of the esophagus were thicker in the Sonali than in the Indigenous chickens. Nonetheless, the Indigenous chickens had a bigger number of lymphocytes. Indigenous chickens had thicker lining epithelium in the proventriculus, whereas Sonali chickens had thicker mucosa. Indigenous chickens showed greater lymphocyte populations than Sonali. Indigenous chickens exhibited taller duodenal and jejunal villi, but Sonali chickens had taller ileal villi. The Sonali possessed wider duodenal and jejunal villi, while Indigenous chickens had wider ileal villi. Because of their scavenging activity, Indigenous people have greater lymphocyte populations in the small intestine. The Sonali possessed the most lymphatic nodules in Meckel’s diverticulum, as well as a higher crypt depth and lymphocyte density. Indigenous chickens had thicker mucosa and Lieberkühn crypts in the caecum, whereas Sonali had a greater lymphocyte count. Indigenous chickens showed larger lymphatic nodules and crypts in the cecal tonsil, whereas Sonali had thicker mucosa, deeper crypts, and a higher lymphocyte population in the colon. Lymphocytes were found scattered throughout the tissues of Sonali and Indigenous chickens. The cells were primarily detected within the lamina propria. Further research with other types of chickens could be undertaken to measure lymphocytes, intraepithelial lymphocytes, and lymphatic nodules. J. of Sci. and Tech. Res. 6(1): 33-44, 2024